Optimizing MSME Technopreneurship: Integration of Industry, Accounting Management, and Sustainable Supply Chains - Yekie Senja Oktora; Indra Lukmana Putra; Triesti Candrawati; Ika Kusumasasti (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2026)
Abstract Technopreneurship based digital technology  framework for micro, small, and medium enterprises (MSMEs), addressing the urgent need for integration across industrial processes, digital accounting management, and sustainable supply chains, which have remained fragmented in practice. The study’s novelty lies in its integrative approach, combining quantitative analysis of MSME performance and technology readiness with qualitative insights into business processes and entrepreneurial behavior, using surveys, in-depth interviews, field observations, and secondary data from financial statements and supply chain documents. The findings produce an adaptive, practical, and measurable operational technopreneurship model, supported by implementation guidelines, an industrial–accounting–supply chain integration map, and policy recommendations, enhancing data-driven decision-making, cost efficiency, and operational risk management. The study’s urgency stems from competitive pressures and market uncertainty, demanding rapid innovation and sustainable resilience. Its theoretical and practical contribution lies in developing the first integrative model enabling cross-sector adoption, downstream scalability, and the strengthening of a sustainable MSME ecosystem.